2020
DOI: 10.3390/atmos11121318
|View full text |Cite
|
Sign up to set email alerts
|

High Latitude Dust Transport Altitude Pattern Revealed from Deposition on Snow, Svalbard

Abstract: High Latitude Dust (HLD) deposition in the surface snow layer in two distant locations in Svalbard (Hornsund and Pyramiden) were collected during the June/July 2019 field campaign and examined in the laboratory. Despite the differences in their climate and topography, both locations are characterised by very similar spatial patterns of the deposition. On the one hand, strong linear negative relationship between the altitude of the sample taken and its concentration was found in low altitude (below 300 m a.s.l.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Dust storms are globally represented in all latitudes as part of the natural dust cycle with positive environmental impacts or as the consequence of disturbed land surface and climate conditions [5,6,[27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Dust storms are globally represented in all latitudes as part of the natural dust cycle with positive environmental impacts or as the consequence of disturbed land surface and climate conditions [5,6,[27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Recent estimations of dust load in central and southern Svalbard from different sources range from 4 g up to 4-5 kg m −2 (Rymer, 2018;Rymer et al, 2022), with the highest values in the Ebba Valley due to frequent dust storms in this area (Strzelecki and Long, 2020). Kavan et al (2020a) found a negative correlation between deposition rate and altitude at Pyramiden (78.71060 • N, 16.46059 • E; western coast of Petuniabukta) and Ariekammen (77.00035 • N, 15.53674 • E; Hornsund area). The pattern was clear up to the altitude of approximately 300 m a.s.l., suggesting the influence of local sources in the lower levels of the atmosphere and long-range transport at higher altitudes.…”
Section: Svalbardmentioning
confidence: 91%
“…Mineral dust is transported from local sources of high-latitude dust (HLD, ≥ 50 • N and ≥ 40 • S, Bullard et al, 2016), low-latitude dust (LLD, mostly 0-35 • N), and the so-called "global dust belt" (GDB, Prospero et al, 2002), defined as extending into the Northern Hemisphere from the western coast of northern Africa over the Middle East (western Asia), central, and East Asia and southwestern North America (Ginoux et al, 2012), with only minor sources in the Southern Hemisphere (Prospero et al, 2002;Ginoux et al, 2012;Bullard et al, 2016;Terradellas et al, 2017). Dust is often associated with hot, subtropical deserts, but the importance of dust sources at the cold, high latitudes has recently increased (Arnalds et al, 2016;Bullard et al, 2016;Groot Zwaafting et al, 2016Kavan et al, 2018Kavan et al, , 2020aBoy et al, 2019;Gassó and Torres, 2019;IPCC, 2019;Tobo et al, 2019;Bachelder et al, 2020;Cosentino et al, 2020;Ranjbar et al, 2021;Sanchez-Marroqin et al, 2020). Dust produced at high latitudes and in cold climates (Iceland, Greenland, Svalbard, Alaska, Canada, Antarctica, New Zealand, and Patagonia) can have regional and global significance (Bullard et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We contributed to an international project, which indicated that the low elevation of Svalbard glaciers drives high mass loss variability (Noël et al 2000), and that they are on their way to total decay, probably even in this century. Part of the story is the dust that accumulates in the glaciers, which effectively lowers the albedo of the snow and ice Kavan et al 2020).…”
Section: About the Departmentmentioning
confidence: 99%